2023
DOI: 10.4103/jos.jos_118_22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 on orthodontic treatment/practice- A systematic review and meta-analysis

Abstract: Coronavirus disease of 2019 (COVID-19), which has affected almost all medical professions, has had a significant negative influence on dental care. Additionally, non-urgent dental procedures were stopped during the epidemic in a number of countries. The purpose of this systematic review was to examine the impact of COVID-19 on individuals who had undergone or are currently having orthodontic treatment in any capacity during/after the pandemic's occurrence. After a thorough search of the online journals, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(29 reference statements)
0
1
2
Order By: Relevance
“…These specific risks should be addressed during the informed consent process, ideally being emphasized through verbal communication by the orthodontist, as revealed by our data. Discrepancies between our study's results and existing data suggest potential influences of socio-demographic parameters and the COVID-19 pandemic, particularly with issues related to the transmission of infectious diseases in the dental clinic [41,42]. These differences underline the dynamic nature of risk communication in orthodontics, whereas external factors and evolving contexts contribute to variations in practitioners' perspectives and practices such as the ones addressed in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…These specific risks should be addressed during the informed consent process, ideally being emphasized through verbal communication by the orthodontist, as revealed by our data. Discrepancies between our study's results and existing data suggest potential influences of socio-demographic parameters and the COVID-19 pandemic, particularly with issues related to the transmission of infectious diseases in the dental clinic [41,42]. These differences underline the dynamic nature of risk communication in orthodontics, whereas external factors and evolving contexts contribute to variations in practitioners' perspectives and practices such as the ones addressed in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…These specific risks should be addressed during the informed consent process, ideally, being emphasized through verbal communication by the orthodontist. Discrepancies between our study's results and existing data suggest potential influences from socio-demographic parameters and the COVID-19 pandemic, particularly with issues related to the transmission of infectious diseases in the dental clinic [62][63][64]. These differences underline the dynamic nature of risk communication in orthodontics, whereas external factors and evolving contexts contribute to variations in practitioners' perspectives and practices such as the ones addressed in our study.…”
Section: Discussioncontrasting
confidence: 70%
“…Another two studies 9 , 10 investigated the impact caused by the coronavirus pandemic on patient care, psychological state, and financial income, but the findings were solely from the perspectives of orthodontists. A systematic review by Alam et al 11 further gathered the results of the impact of COVID-19 on orthodontic treatment. This review concluded that there was a significant impact on every sphere of the patients’ lives like previously mentioned, but the level differed between orthodontic patients during the first wave, early stage, and later stage of the pandemic.…”
Section: Introductionmentioning
confidence: 99%